Rethinking progress and ensuring a secure future for all: what we can learn from the crisis = Repenser le progrès et assurer un avenir pour tous: les leçons de la crise - Council of Europe (Strasbourg, 2011)
"Europe is bearing the full load of globalisation. Besides population movements on an unprecedented scale, awareness of our interdependence and competition for natural resources are increasing. These changes affect not only institutions and individuals on social and economic grounds, but also, more decisively, public opinion. People have a vague sense of insecurity, fear and anxiety, fuelling doubts about the future: never before has confidence been so lacking in the modern era.